Biomethane production and palm oil mill effluent treatment by co-cultivation of Nannochloropsis oculata - Ahmad, A. (Trans Tech Publications Ltd, 2014)
Co-cultivation of Nannochloropsis oculata with Oil Palm Empty Fruit Bunches (OPEFB) was explored for biomethane production and POME treatment. The experimental results were analyzed and modeled using a multilevel factorial design (MFD) of response surface methodology (RSM). Maximum specific biogas production rate (0.126 m3 kg-1 COD day-1) and biomethane production (4813.0 mL CH4 L-1 POME day-1) were achieved with 2 mL mL-1 POME of microalgae and OPEFB 0.12 g mL-1 POME. POME treatment after 3 and 7 days with microalgae achieved higher removal efficiency (56-98) of COD, BOD and TOC, than without microalgae. Â© 2014 Trans Tech Publications, Switzerland.